Analgesic effect of watching TV during venipuncture. Issue 12 (18th August 2006) - Bellieni, C V; Cordelli, D M; Raffaelli, M; Ricci, B; Morgese, G; Buonocore, G
Abstract : Aims: To assess the analgesic effect of passive or active distraction during venipuncture in children. Methods: We studied 69 children aged 7–12 years undergoing venipuncture. The children were randomly divided into three groups: a control group (C) without any distraction procedure, a group (M) in which mothers performed active distraction, and a TV group (TV) in which passive distraction (a TV cartoon) was used. Both mothers and children scored pain after the procedure. Results: Main pain levels rated by the children were 23.04 (standard deviation (SD) 24.57), 17.39 (SD 21.36), and 8.91 (SD 8.65) for the C, M, and TV groups, respectively. Main pain levels rated by mothers were 21.30 (SD 19.9), 23.04 (SD 18.39), and 12.17 (SD 12.14) for the C, M, and TV groups, respectively. Scores assigned by mothers and children indicated that procedures performed during TV watching were less painful (p<0.05) than control or procedures performed during active distraction. Conclusion: TV watching was more effective than active distraction. This was due either to the emotional participation of the mothers in the active procedure or to the distracting power of television.